Relationship Between Information Sources and Pregnant Women’s Interest in Undergoing PMTCT - Ryana Kartika Hestiningtyas; Nur Azizah Indriastuti (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
HIV/AIDS remains a serious health problem in Indonesia, particularly in relation to its impact on mothers and infants. Mother-to-child transmission of HIV can be prevented through the Prevention of Mother-to-Child Transmission (PMTCT) program. The success of this program is influenced by pregnant women's access to quality and easily understood information sources, which can increase their interest and behavioral tendencies in participating in PMTCT services. This study aims to determine the relationship between information sources and pregnant women's interest in PMTCT at the Gamping I Community Health Center in Yogyakarta. The study used a cross-sectional design with Spearman Rank Correlation analysis. The study respondents were pregnant women who met the inclusion criteria. The results showed that most respondents were aged 20–35 years (52.8%), had a high school/vocational high school education (68%), were unemployed (88.8%), were multigravida (51.2%), and were in their second trimester (48.0%). Most respondents had good information sources (52.8%) and had a high interest in PMTCT (78.4%). Statistical tests showed a significant relationship between information sources and pregnant women's interest in PMTCT (r = 0.350; p < 0.001). This finding suggests that the quality and access to information sources play a significant role in increasing pregnant women's interest in PMTCT. Promotional and preventive efforts need to focus on improving the quality and access to PMTCT information through various media and direct approaches by health workers.